Challenges and recommendations for enhancing digital data protection in Indian Medical Research and Healthcare Sector - Anubhuti Sood; Deepika Mishra; Varun Surya; Harpreet Singh; Rajesh Sundaresan; Debnath Pal; Raghu Dharmaraju; Rohit Satish; Shashwat Mishra; Nishant A. Chavan; Soham Mondal; Pavan Duggal; et al. (npj Digital Medicine)
Abstract The Digital Personal Data Protection Act (DPDPA), 2023 of India provides a regulatory framework for use and security of personal digital data. However, instances, wherein the patients consult the clinicians via digital means of communication: the implications of DPDPA, 2023 for the medical personnel remain unclear. This paper critically discusses the gray areas encountered in the Indian medical ecosystem and DPDPA, 2023 and; lists the recommendations to address them.